Floral divergence in closely related Leucospermum tottum (Proteaceae) varieties pollinated by birds and longproboscid flies - Johnson, C.; He, Tianhua; Pauw, A. (Kluwer Academic Publishers, 2014)
The Proteaceae are renowned for their floral diversity but surprisingly the role of pollinators in driving evolutionary divergence in this family has been underexplored. Here we focus on recently diverged taxa to gain insight into the processes that generate diversity by testing whether two varieties of Leucospermum tottum might have originated by pollinator mediated adaptive divergence. L. tottum var. tottum has pale salmon-coloured horizontally-oriented flowers, long nectar tubes, and small volumes of concentrated nectar. L. tottum var. glabrum has red and yellow vertically oriented flowers, short nectar tubes, and large volumes of dilute nectar. Despite the morphological divergence, the varieties are indistinguishable using eight molecular markers, indicating a very early stage of differentiation. Consistent with their morphologies, L. tottum var. tottum is pollinated by long-proboscid flies (Philoliche rostrata and Philoliche gulosa), Cape sugarbirds (Promerops cafer), and, to a lesser extent, by Orange-breasted sunbirds (Anthobaphes violacea), whereas, L. tottum var. glabrum is pollinated only by Orange-breasted sunbirds. A. violacea visits both varieties, but makes more frequent contact with pollen presenters when foraging on L. tottum var. glabrum. The exclusion of birds caused a steeper reduction in seed production in L. tottum var. glabrum than in L. tottum var. tottum, consistent with specialization for bird-pollination in this variety. Additionally, L. tottum var. glabrum exhibits autogamy, whereas L. tottum var. tottum does not. Floral divergence between the two L. tottum varieties corresponds with divergence in pollinator use.